Ground-Station Based Software-Defined LEO Satellite Networks - Xia, Dan; Zheng, Xiaolong; Duan, Pengrui; Wang, Chaoyu; Liu, Liang; Ma, Huadong (2019 IEEE 25th International Conference on Parallel and Distributed Systems (ICPADS), 2019)
Low Earth Orbit (LEO) satellite networks play an indispensable role in global communications. To cope with the dynamic nature of the LEO networks, a flexible management architecture that can provide low-latency configuration and routing services is desired. Recent advances of Software Defined Networks (SDN) inspire researches using geostationary satellites, GEO, as the controllers to build the SDN solutions for LEO satellite networks. However, GEO-based solutions inevitably face the bottleneck problem because all the routing requests have to be processed and forwarded by a limited number of GEO satellites. In this paper, we propose HTCA, a Hierarchical Terrestrial Controllers Architecture based on SDN that reuses the ground stations instead of dedicated GEO satellites to establish a more scalable control plane. But the limited coverage of a ground station brings about design challenges for consistent network management and seamless routing service. HTCA adopts an online network view integration method to support flexible and consistent management. A load-aware routing method is also designed for HTCA to provide seamless and low-latency routing service. The experiment results demonstrate that HTCA can achieve agile configuration and reduce the instruction update time by 86.87%, compared with the GEO-based solution.